Relationship between Attention Capacity and Hand–Eye Reaction Time in Adolescents between 15 and 18 Years of Age - Huerta Ojeda, Álvaro Cristian.; Lizama Tapia, Patricio.; Pulgar Álvarez, Jaime.; González Cruz, Claudia.; Yeomans Cabrera, María Mercedes.; Contreras Vera, Juan. (MDPI, 2022)
Some experiences demonstrate a direct correlation between attention capacity and reaction capacity. However, the evidence from adolescents enrolled in the Chilean school system is scarce. The purpose of this study was to determine the relationship between attention capacity and hand–eye reaction time (RT) in adolescents between 15 and 18 years of age. Thirty-one adolescents participated voluntarily in this study. The variables were: attention capacity, evaluated through the Evalúa-10 battery (item 1.1), and hand–eye RT, assessed through a simple RT test (SRT) and complex RT (CRT). The relationship between the variables was performed through Pearson’s correlation. Comparisons between males and females were performed with the t-test for independent samples (p ˂ 0.05). There was a moderate correlation between attention and CRT (r = −0.43), a very high correlation between attention and SRT in males (r = −0.73), and between attention and CRT in females (r = −0.73). Between males and females, there was no difference in attention (p ˃ 0.05), while males showed better RT in all tests (p ˂ 0.05). Attention positively influences hand–eye RT in both males and females. Likewise, male adolescents present better hand–eye RT than their female peers.
Keywords: Executive functions; Concentration; Reaction; Reaction capacity; Adolescentes; Attention